Double-layer electrospun fibers with integrated gas-selective and bioactive functions for the preservation of perishable fruit - Wei Liu; Lin Wang; Kunyi Wang; Xinzhi Liang; Ting Liu; Jingxuan Tan; Xiaoyong Qiu; Jingcheng Hao (Food Research International, 2026)

Wettability-gradient bilayer nanofiber membranes for regulating microbial, moisture microenvironment and directional water transport in food preservation - Lin Wang; Wei Liu; Xianrui Chen; Zhenzhen Wu; Zeyi Wang; Xiuqing Guan; Huaiwen Zhang; Jingcheng Hao (Food Control, 2026)

Advancement of a multifunctional composite coating encapsulating CGA-Zn2+ MPN nanoparticles for enhanced postharvest fruit preservation - Wei Liu; Lin Wang; Jingcheng Hao (Food Control, 2026)

CuI additive induced co-regulation of ion transport and interfacial chemistry in poly(ethylene oxide)-based solid-state electrolytes for improved battery performance - Kepan Yan; Xuexiao Chen; Haoliang Huang; Zicong Yu; Jingcheng Lu; Zhipeng Yu; Sitaramanjaneya Mouli Thalluri; Jinfeng Zeng; Wei Wang; Fei Lin; Yijuan Li; Weicai Zhang; et al. (Chemical Engineering Journal, 2026)

Experimental Study on Suppression and Mechanism of Sloshing Impact Pressure by Vertical Slat Screens Under Broadband Horizontal and Vertical Excitation - Liting Yu; Xiaoqian Luo; Jingcheng Lin; Jie Fan; Heng Jin (Journal of Marine Science and Engineering, 2026)
Sloshing-induced impact pressure is a key damage factor for marine liquid tanks. While research aimed at overcoming screen failure in sloshing suppression under high-frequency excitation has focused on wave height, the dataset of impact pressure remains lacking. Moreover, the pattern of pressure suppression under broadband excitation remains unclear. The primary contribution of this work is the first experimental dataset of impact pressure with vertical slat screens under broadband horizontal and vertical excitation. Second, it reveals pressure suppression patterns by screens across varying excitation frequencies and screen numbers. The results demonstrate that vertical slat screens can effectively suppress pressure. First, screen position matters more than number, proving that suppression is dominated by modal disturbance. Second, wave-height suppression does not reliably represent pressure suppression. Pressure suppression is systematically weaker. An exception occurs under vertical excitation, where pressure suppression can be stronger even when wave-height suppression fails. The results highlight the suppression mechanism dominated by modal disturbance and the instability inherent to parametric sloshing. Wave height, reflecting global potential energy, is effectively suppressed by modal disturbance. Pressure, originating from local kinetic energy, can be effectively suppressed by both modal disturbance and vortex dissipation.

Forecasting of large-scale tea anthracnose in mountainous region of China though integration of multi-source habitat information with spatiotemporal phenological corrections - Yujuan Huang; Huiqin Ma; Cong Xu; Lin Yuan; Jingfeng Huang; Zijing Jin; Jingcheng Zhang (European Journal of Agronomy, 2026)

Synergistic 3D nanofibers for enhanced microbial control and moisture regulation in fruit preservation - Lin Wang; Wei Liu; Xianrui Chen; Zhenzhen Wu; Nitong Bu; Huimin Xiao; Chen Ma; Jingcheng Hao (Chemical Engineering Journal, 2025)

Integrating UAV and high-resolution satellite remote sensing for multi-scale rice disease monitoring - Lin Yuan; Qimeng Yu; Lirong Xiang; Fanguo Zeng; Jie Dong; Ouguan Xu; Jingcheng Zhang (Computers and Electronics in Agriculture, 2025)

Microplastics in wild fish in the Three Gorges Reservoir, China: A detailed investigation of their occurrence, characteristics, biomagnification and risk - Yizhi Pei; Ying Lin; Jinsong Guo; Kongyan Luo; Jianyong Wu; Jingcheng Wu; Wenhao Yang; Junmin Gao (Journal of Hazardous Materials, 2024)

The impact of the urban landscape on PM2.5 from LCZ perspective: A case study of Shenyang - Ye Lin; Xin An; Jingcheng Yuan; Jing Yuan; Boyu Chen (Urban Climate, 2024)

Design and application of Cd2+ polypeptide fluorescent probes based on Aggregation Induced Emission (AIE) - Jiang Zhou; Xuejiao Wang; Dajiang Wang; Liangchao Yuan; Junlei Hao; Jingcheng Hou; Jiang Wu; Pengcheng Lin (Journal of Molecular Histology, 2024)

Spatial relationship between pre-harvest hail and the impact from the wheat streak mosaic disease complex by using remote sensing data - Dongmei Chen; Gary L. Hein; Rebecca Adams-Selin; Lin Wang; Jingcheng Zhang; Xianfeng Zhou; Huiqin Ma; Justin McMechan; Yeyin Shi (Crop Protection, 2024)

Portable multichannel detection instrument based on time-resolved fluorescence immunochromatographic test strip for on-site detecting pesticide residues in vegetables - Rui Xu; Yaodong Xiang; Zheng Shen; Gaozhen Li; Jiashuai Sun; Peiyu Lin; Xiaofeng Chen; Jingcheng Huang; Haowei Dong; Zhenying He; Wenzheng Liu; Lu Zhang; et al. (Analytica Chimica Acta, 2023)

Hydrogels as the plant culture substrates: A review - Lin Ma; Chunxiao Chai; Wenna Wu; Ping Qi; Xingcen Liu; Jingcheng Hao (Carbohydrate Polymers, 2023)

Efficient degradation of triclosan by aluminium acetylacetonate doped polymeric carbon nitride photocatalyst under visible light - Danyan Sun; Xiaohu Lin; Jingcheng Xu; Zhibo Lu; Juwen Huang; Shiyi Li; Luiza C. Campos (Journal of Environmental Chemical Engineering, 2023)

Using high spatial resolution satellite imagery for mapping powdery mildew at a regional scale - Lin Yuan; Ruiliang Pu; Jingcheng Zhang; Jihua Wang; Hao Yang (Precision Agriculture, 2016)

Hyperspectral measurements of severity of stripe rust on individual wheat leaves - Jinling Zhao; Linsheng Huang; Wenjiang Huang; Dongyan Zhang; Lin Yuan; Jingcheng Zhang; Dong Liang (European Journal of Plant Pathology, 2014)

Evaluation of spectral indices and continuous wavelet analysis to quantify aphid infestation in wheat - Juhua Luo; Wenjiang Huang; Lin Yuan; Chunjiang Zhao; Shizhou Du; Jingcheng Zhang; Jinling Zhao (Precision Agriculture, 2013)